2020
DOI: 10.1101/2020.09.14.295972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory specificity is linked to repetition effects in event-related potentials across the lifespan

Abstract: Our memories depend on our brain's ability to form internal representations of relevant aspects of the world that can later be retrieved. The specificity with which past experiences can be remembered varies across the lifespan, possibly due to differences in how precisely information is encoded. This memory formation can be investigated through repetition effects, the common finding that neural activity is altered (suppressed or enhanced) when stimuli are repeated. However, whether differences in this indirect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 133 publications
(221 reference statements)
2
1
0
Order By: Relevance
“…Less pronounced or no age-related deficits in item recognition memory, compared to, for example, associative memory, are not uncommon, especially under incidental encoding conditions (cf. Old and Naveh-Benjamin, 2008;Sommer et al, 2020). Nevertheless, older adults often tend to respond "old" more frequently than younger adults, contributing to their higher rates of false memories (Koutstaal and Schacter, 1997;Schacter et al, 1997;Fandakova et al, 2013Fandakova et al, , 2020 which was also observed in the present study.…”
Section: Age-related Neural Dedifferentiation Coexists At Different Rsupporting
confidence: 78%
“…Less pronounced or no age-related deficits in item recognition memory, compared to, for example, associative memory, are not uncommon, especially under incidental encoding conditions (cf. Old and Naveh-Benjamin, 2008;Sommer et al, 2020). Nevertheless, older adults often tend to respond "old" more frequently than younger adults, contributing to their higher rates of false memories (Koutstaal and Schacter, 1997;Schacter et al, 1997;Fandakova et al, 2013Fandakova et al, , 2020 which was also observed in the present study.…”
Section: Age-related Neural Dedifferentiation Coexists At Different Rsupporting
confidence: 78%
“…With regard to memory formation, while we observed generally similar mechanisms of memory encoding in older and younger adults in case of successful memory (see also (Sommer et al, 2020;Strunk & Duarte, 2019), older adults more often form memories that are of lower quality than those of younger adults. For example, we found that both age groups showed reliable oscillatory subsequent memory effects.…”
Section: Discussionsupporting
confidence: 69%
“…alpha/beta band, tend to form memory representations that have undergone less deep elaboration during encoding and may as a consequence contain fewer details. In other words, while the general mechanisms that underlie successful memory formation appear not to change across adulthood, the probability to successfully engage memory formation operations does seem to deteriorate as well as the level of detailedness or specificity of memories (see alsoSommer et al, 2020).Recent advances in neuroimaging analysis techniques allow characterizing memories with regard to their informational content, ultimately improving investigations of the detailedness of memories. Representational pattern analysis (RSA) is a multivariate analysis technique that describes neural activation patterns between stimuli in terms of their similarity or distance in geometric space(Kriegeskorte & Diedrichsen, 2019;Kriegeskorte & Kievit, 2013).…”
mentioning
confidence: 99%